2015
DOI: 10.1093/mnras/stv1017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Kepler B stars: rotational modulation and Maia variables

Abstract: We examine 4-yr almost continuous Kepler photometry of 115 B stars. We find that the light curves of 39 percent of these stars are simply described by a low-frequency sinusoid and its harmonic, usually with variable amplitudes, which we interpret as rotational modulation. A large fraction (28 percent) of B stars might be classified as ellipsoidal variables, but a statistical argument suggests that these are probably rotational variables as well. About 8 percent of the rotational variables have a peculiar perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 36 publications
(52 reference statements)
2
99
0
Order By: Relevance
“…KIC 3240411 was classified as the SPB/β Cep hybrid pulsator by Balona et al (2011) who found in total more than 100 frequency peaks based on the analysis of Q0-Q4 Kepler data. This classification was confirmed by Balona et al (2015) who extracted a large number of frequencies with the most prominent ones below 2 d −1 and many very lowamplitude peaks up to 17 d −1 .…”
Section: The Star Kic 3240411mentioning
confidence: 65%
See 1 more Smart Citation
“…KIC 3240411 was classified as the SPB/β Cep hybrid pulsator by Balona et al (2011) who found in total more than 100 frequency peaks based on the analysis of Q0-Q4 Kepler data. This classification was confirmed by Balona et al (2015) who extracted a large number of frequencies with the most prominent ones below 2 d −1 and many very lowamplitude peaks up to 17 d −1 .…”
Section: The Star Kic 3240411mentioning
confidence: 65%
“…Photometric data from the projects such as MOST, CoRoT, Kepler, and recently BRITE, revealed huge multi-periodicity ⋆ E-mail: szewczuk@astro.uni.wroc.pl (WS) and diversity of pulsations of B-type stars. In particular, we learnt that a lot of them, if not the vast majority, are hybrid pulsators of SPB/β Cep or β Cep/SPB type (Degroote et al 2010;Balona et al 2011;McNamara et al 2012;Pápics et al 2012Pápics et al , 2014Pápics et al , 2015Pápics et al , 2017Balona et al 2015;Pigulski et al 2016;Kallinger et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An ideal training set would consist of a set of known variable stars from the K2 mission, to which we can fit the classifier. Some previous classification work on K2 has been done (for B stars Balona et al 2015, for eclipsing binaries LaCourse et al 2015, and in the previous version of this catalogue). These sources however suffer from either small numbers, only being applicable to a few variable types, or in the Armstrong et al (2015) case using variability classes derived from the light curves rather than externally recognized types.…”
Section: Training Setmentioning
confidence: 99%
“…A new list of target objects is defined for each campaign: the Ecliptic Plane Input Catalog 3 (hereafter, EPIC). Despite the changes introduced in K2 mission, several notable results have been achieved, from exoplanet discovery and characterization (e.g., Crossfield et al 2015;Foreman-Mackey et al 2015;Vanderburg et al 2015) to asteroseismology (Hermes et al 2015;Stello et al 2015) and stellar astrophysics (Armstrong et al 2015;Balona et al 2015;Kraus et al 2015;LaCourse et al 2015).…”
Section: Introductionmentioning
confidence: 99%